SISTEM APLIKASI E-PASAR UNTUK UMKM DI KABUPATEN KUNINGAN BERBASIS WEBSITE DENGAN METODE E-BISNIS - Deny Hidayatullah; Riki Rivaldhy Syam (NUANSA INFORMATIKA, 2012)
This final report is the result of writer’s analyses on several UMKM samples at Kuningan district. Currently, most of UMKM at Kuningan district still uses manual system in the transaction and marketing. It uses Billboards, banner, and pamphlet.Based on the identification of existing problem, the writer designs and makes application system that can support UMKM in doing online transaction and marketing.Because the transactions are done online then application system is constructed based on website and the method applied is e-business.By using online application system will make easier for UMKM in expanding their sales networks because it can reach all internet users.Kata Kunci: E-Pasar, UMKM, E-Bisnis, Website